The Story of Maryam - "Khan, Saniyasnain" (China; Goodword Books, 2024)
This beautifully illustrated board book introduces children to some of the greatest stories from the Quran in a simple and engaging way. Each story is carefully chosen to convey timeless lessons of faith, honesty, patience, kindness, and trust in Allah. Told in age-appropriate language, it helps young readers understand the wisdom behind these stories and how they relate to everyday life. With vibrant illustrations and gentle narration, the book captures children's attention while nurturing their spiritual and moral growth. Perfect for toddlers and preschoolers, the sturdy board book design ensures durability through repeated reading. It$1 (Bs an ideal tool for parents and caregivers to begin early Islamic education in a fun and meaningful way.s
Keywords: Prophets Story